(untitled) (Castilla. Estudios de Literatura, 2012)
A short story titled “En los tentáculos de los siglos” and signed by Isabel Inghirami, pseudonym with which Maria Teresa Leon published his first writings, it appeared in the pages of the Revista de la Raza, in February and March of 1925. This story is similar to these included in La bella del mar amor. Cuentos castellanos (1930), that depends on the literary and the artistic tradition, specially on the last. In this forgotten story, is evident the influence of the images provided by the painting and the photography in the decades of 1910’s and 1920’s, and the influence of the Exhibition of regional customes celebrated in April of 1925, too.